CD44 is a macrophage receptor for TcdB from Clostridioides difficile that via its lysine-158 succinylation contributes to inflammation - Zhuo Chen; Wenzi Zhang; Danni Wang; Ruiqin Luo; Yuexin Yao; Xiaoyang Tao; Lu Li; Qin Pan; Xiaoming Sun (Gut Microbes, 2025)
Toxin B (TcdB) is a critical virulence factor in Clostridioides difficile-associated disease (CDAD), which activates macrophages to promote inflammation and epithelial damage. However, the mechanism by which TcdB targets inflammation-related receptors on the macrophage surface and the underlying molecular mechanisms remain unknown. The frizzled-binding domain of TcdB (TcdB-FBD) is a promising target of TcdB. Here, FBD was found to trigger macrophage inflammation, similar to TcdB, but did not induce cytotoxicity. Thus, using FBD as a bait protein, macrophage CD44 was identified as an inflammation-related receptor for TcdB/FBD. The role of CD44 was confirmed by CRISPR/Cas9-mediated gene knockout in macrophages and CD44 knockout mice. Using 4-D label-free succinylation quantitative modification proteomics, we demonstrated that TcdB/FBD binds to CD44 in macrophages, promotes CD44 K158 succinylation via SUCLG2 suppression, and enhances NF-κB translocation/transcriptional activity, thereby driving inflammation. Finally, blocking the binding of TcdB to CD44 was demonstrated as a favorable strategy for inhibiting TcdB-mediated macrophage inflammation. This study not only provides a new therapeutic target for the prevention and treatment of CDAD but also elucidates a new molecular mechanism underlying the inflammatory effect of TcdB via the TcdB/FBD-CD44 axis.